Correlation Analysis of Enverontmental Cd Exposure in Liver and Meat of Broiler Chicken - Amelia Ramadhani Anshar; Huda Salahudin Darusman; Hera Maheshwari (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2018)
Cadmium (Cd) belongs to heavy metal with high anthropogenic pollutant and non-essential to physiological funtion. Regular intake of consuming Cd leads to physiological disorders in poultry animal as well as humans as one who consume it. The aim of this study was to analyze the profile of Cd content in environmental samples (poultry feed and water) and it correlated with the degree of contamination in broiler tissues. In this study, 30 samples of feeds and water samples along with 60 samples of liver and muscle have been examined. The results showed that the feed was indicated to Cd between 0.009-0.202 mg / kg and in the water between 0.0068-0.0096 mg / l. Cd in the livers and muscles was then positively contaminated by Cd between 0.438-0.565 mg / kg and the levels was significantly different (p <0.05) among organs. A strong positive correlation was found between Cd and water levels in liver (r = 0.896). In contrast, a weaker positive correlation (r = 0.596) was found in the water and muscle. In conclusion, Cd contamination in feed and water correlated positively with the increasing amount of the cadmium level in organs.